Les sciences sociales à la découverte de l’homosexualité - Gayle S. Rubin (Genre, Sexualité et Société)
Social science work on urban gay communities is not as newly emergent as it is often believed to be. The author analyzes the connections uniting the papers presented in this special issue to the sociological trends that gave rise to them. She retraces the genealogy of work in the social sciences that treats homosexuality, reestablishes the context of the emergence of the compiled texts, and highlights their qualities and contributions, taking particular note of their influence on work produced during the following decades.